Stability of buildings. Part 3, - Gardner, A. (Engineer) (Institution of Structural Engineers, 2015)
Part 3 introduces structural shear walls considering their form, behaviour and construction options. Theory, analysis and modelling, and design are each considered in turn. Of these, the topic of design is intentionally broad with sub-sections for different materials including reinforced concrete, masonry, steel and timber. This Guide also recognises the real-life design challenges of modern buildings and identifies some of the common non-structural requirements of walls that impact on the structural engineer's design decisions. It does not attempt to be a prescriptive manual. Instead it gives an overview and tends to navigate readers towards sources of further reading. The series is an introduction written primarily for graduate design engineers, particularly those approaching a professional review. The content is largely applicable to all buildings, whether permanent or temporary, static or deployable, and is considered to have international relevance. --